Epidemiology of variant transthyretin amyloidosis at a reference center in Argentina - Saez, María Soledad (2021)
Background: In Argentina, there is limited data of prevalence of variant transthyretin amyloidosis (ATTRv) and phenotype-genotype correlation. The laboratory of Hospital Italiano de Buenos Aires (HIBA) is a reference center for transthyretin (TTR) gene sequencing. The Institutional Amyloidosis Registry (RIA) enable us to characterize people with ATTRv. Our aim was to describe the prevalence of TTR mutations at a reference center in Argentina and the phenotypic presentations of patients with ATTRv included in an institutional registry. Methods: Retrospective cohort study of consecutive patients with genetic variants in the TTR gene identified from 2012 to 2019 in the laboratory. We collected all phenotypic characteristics of patients who were clinically evaluated by HIBA doctors. Results: Five hundred seventy-six patients tested, 141 positive: p.Val50Met 107, p.Thr80Ala 16, p.Ala117Ser 9, p.Phe84Leu 2, p.Ile127Val 2, p.Tyr134Cys 2, p.Ala56Pro 2, p.Val142Ile 1. Only 20 patients were clinically evaluated. The mean age at diagnosis was 54 years; 70% had family history with a pedigree median of 4. Mutations were p.Thr80Ala 9, p.Val50Met 6, p.Ala56Pro 2, p.Val142Ile 1, p.Phe84Leu 1, and p.Tyr134Cys 1. Eleven patients presented polyneuropathy, 11 had gastrointestinal compromise, six patients had autonomic compromise, six presented cardiac symptoms and four patients presented ocular involvement. Conclusion: We present the first prevalence report of TTR mutations in a reference center of amyloidosis in Argentina. The most frequent genetic variant was p.Val50Met. Our data show considerable phenotypic heterogeneity in the patients with ATTRv.